Cultivo de consórcios granulares algal-bacterianos em fotobiorreatores em batelada sequencial: estabilidade e desempenho operacional. - Cordeiro, Giancarlo Lavor (2024)
Aerobic granular sludge (AGS) technology stands out among the promising approaches for biological wastewater treatment, with only a few operational challenges. Some of these challenges can be mitigated by integrating microalgae into the system, forming consortia with bacteria known as algal-bacterial granular sludge (ABGS) or photogranules. Thus, this study aimed to investigate the impact of microalgae on the formation, stability, and removal of carbon (C), nitrogen (N), and phosphorus (P) from ABGS in the treatment of synthetic domestic wastewater with high organic load. A factorial design was proposed to define the optimal lighting conditions, with photoperiod and light intensity as independent variables and optical density (OD) as the response. The reactors had a volume of 8 L with 6-h cycles and a 50% volumetric exchange rate, using a settling time reduction strategy from 20 to 15, 10, and 5 min in phases I, II, III, and IV, respectively. Reactors R1 and R2 were inoculated with sludge from a University of Cape Town (UCT) system and the microalgae species C. vulgaris and S. obliquus, respectively, while R3 was inoculated only with sludge from the UCT system, serving as the control. The systems were fed with synthetic domestic wastewater containing 850 mg·COD·L-1, 50 mg·N·L-1 e 10 mg·P·L-1. The optimal lighting conditions were established at 150 μmol·m-2·s-1 of light intensity and a photoperiod of 14 h of light and 10 h of dark. In the granulation process, R1 and R2 presented granulation in phase IV (5 min settling) on days 96 and 71, respectively, while R3 remained ungranulated. R2 also presented better stability regarding settleability. Regarding the extracellular polymeric substances, the protein fraction (PN) was higher than that of polysaccharides (PS) in all reactors throughout the experiment, with PN/PS ratios of 3.88, 4.28 and 5.14 for R1, R2 and R3. The systems presented stability coefficients (S) of 38.1%, 45.8% and 38.3% for R1, R2 and R3, respectively, indicating low resistance. The removal efficiencies of COD, N and P were > 97%, > 70% and ~30%, respectively, in the three reactors. Respirometry tests indicated that the ABGS consortium favored the activity of heterotrophic and autotrophic ammonia-oxidizing bacteria. It was possible to cultivate ABGS inoculated with the green microalgae C. vulgaris and S. obliquus in synthetic domestic wastewater under conditions of high organic load (> 800 mg COD·L-1), suggesting that the presence of microalgae favored the granulation process. The reactor inoculated with S. obliquus obtained complete granulation in less time, larger granules and better settleability.